International trade : causes and consequences : an empirical amd theoretical text - Borkakoti, Jitendralal (Basingstoke : MacmillanBusiness, 1998)
This book is about: International trade in the Real World and the Theorretical issues; Economic methodology; The classical view; Sources of International trade; ...
Keywords: Ngoại thương; International trade; Econometric models; International trade; International trade -- Econometric models